The muslim's need for tafsir | حاجة المسلم إلى التفسير - Ahmad Kusyairi Suhail (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2008)
Human beings need tafsir (interpretation) tounderstand the Qur'an properly and correctly so thatthey can apply its values for their worldly andhereafter life. This conclusion formulated by thewriter is based on his study on several verses of theQur'an. In his study the writer applies thematicmethod of tafsir.